Plants used by kamar, gond and halba tribe of Dhamtari district of Chhattisgarh for relief of sickle cell disease - Acharya, V; Sharma, V; Patra, P K; Naik, M L; Kanungo, V K (Recent Research in Science and Technology, 2012)
In Chhattisgarh state sickle cell disease is reported in many tribal communities. Some of these tribes reside in Jawwara, Dugali, Nagari, Sihawa, which are the remote forest areas of Dhamtari. They totally dependent on forest and forest produce for their livelihood and ailments. Gond is the dominant tribe of C.G. as well as of India, Halba is an advance tribe and Kamar tribe is declared as one of the most primitive tribe of India in sixth five year plan. During Ethnobotanical survey it was observed that for cure ailments they used their traditional herbal medicines and use wild vegetables fruits and foods such as under ground rhizome of Curcuma angustifolia (Tikhur) fresh tuberous roots of Abelmoschus crinitus (Dotokand) flowers of Indigofera cassoides (Ghirgholi) and boiled seeds of Dolichos biflorus (Kulthi), unriped fruits of Carica papaya (Papita) and Musa paradisica (Kela) to improve their general health conditions. In traditional herbal medicines the whole plants as decoction of Andrographis paniculata. (Bhuineem) dried roots of Scoparia dulcies boiled, tubers of Dioscorea sps, dried powder of Chlorophytum tuberosum (Safed Musli) are used for general health problems. In the present study 20 sickle cell homozygous patients (identified during screening process of sickle cell project coordinated by Department of Biochemistry. Pt. Jawaharlal Nehru Memorial Medical College. Raipur, C.G.), are taken under consideration to check the level of fetal haemoglobin and haemoglobin after giving traditional herbal treatment by traditional medicine man for further six months because most of the health problems are managed by local traditional healers. After the stipulated time the fetal hemoglobin and hemoglobin status will be seen so as to see the role of traditional herbs taken by the tribal people.Â  Â 